KARAKTERISASI ANTIOKSIDAN EKSTRAK DAUN SELEDRI (APIUM GRAVEOLENS) DAN PENETAPAN KADAR FLAVONOID TOTAL DENGAN METODE MASERASI - Rhahmasari Ismet; Rusnia Junita Hakim; Wiwik Indrawati; Dina Adelina; Agustina Dyah Setyowati; Jufrinaldi Jufrinaldi; Budhi Indrawijaya; Irman Ansari Adlin; Indri Lutviyana Sari; Tina Marlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Hypertension is a chronic medical condition characterized by elevated blood pressure levels exceeding the normal threshold (≥120/80 mmHg), which can lead to damage in vital organs such as the heart, kidneys, brain, and blood vessels. One promising alternative treatment involves the use of herbal remedies, such as celery leaves (Apium graveolens L), which are known to contain various vitamins, minerals, and antioxidant compounds including beta-carotene, lutein, zeaxanthin, and flavonoids such as luteolin and apigenin—both of which are recognized for their antihypertensive properties. This study aims to characterize the antioxidant activity and determine the flavonoid content of celery leaf extract using the maceration method. Extraction was conducted with varying ratios of solvent to leaf powder (1:10, 1:15, and 1:20) and different maceration durations (24, 36, and 48 hours). The best yield was obtained at a ratio of 1:15 with 24 hours of maceration, resulting in an extract with a pH of 6, density of 0.869 g/mL, and viscosity of 15.75 cP. Antioxidant activity analysis revealed an IC₅₀ value of 66.3774 mg/mL, while total flavonoid content reached 17.97 mg/g. These findings suggest that celery leaves possess potential as a natural antihypertensive agent due to their antioxidant activity and flavonoid content.Keywords: Hypertension, Celery Leaves, Antioxidants, Flavonoids and Maceration